The Loyalty Triangle: Service Quality, Perceived Product Quality, and Marketing Mix Driving Pet-Care Customer Loyalty - Pangestu, Andaru Dwi; Hartoyo, Hartoyo; Simanjuntak, Megawati (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Pet-care markets are increasingly competitive, making customer loyalty a strategic imperative for retail sustainability. This study offers a nascent integrative contribution by jointly modeling service quality, product quality, and marketing mix as antecedents of loyalty through the sequential mechanisms of satisfaction and trust, a configuration rarely examined within a unified framework. Using survey data from 357 customers of a leading pet-care retailer and analyzing them with PLS-SEM in SmartPLS 4, the results demonstrate that service quality, product quality, and marketing mix enhance satisfaction, which fosters trust and strengthens loyalty. Trust further exerts a direct positive influence on loyalty, while satisfaction and trust operate as pivotal mediators. Managerially, firms should prioritize consistent service excellence, reliable product performance, and strategically aligned marketing programs to cultivate satisfaction and trust as foundations of durable customer loyalty.